Residence rule flexibility and descent groups dynamics shape uniparental genetic diversities in South East Asia. Issue 3 (23rd January 2018) - Ly, Goki; Alard, Bérénice; Laurent, Romain; Lafosse, Sophie; Toupance, Bruno; Monidarin, Chou; Diffloth, Gérard; Bourdier, Frédéric; Evrard, Olivier; Pavard, Samuel; Chaix, Raphaëlle
Abstract: Objectives: Social organization plays a major role in shaping human population genetic diversity. In particular, matrilocal populations tend to exhibit less mitochondrial diversity than patrilocal populations, and the other way around for Y chromosome diversity. However, several studies have not replicated such findings. The objective of this study is to understand the reasons for such inconsistencies and further evaluate the influence of social organization on genetic diversity. Materials and Methods: We explored uniparental diversity patterns using mitochondrial HV1 sequences and 17 Y‐linked short tandem repeats (STRs) in 12 populations ( n = 619) from mainland South–East Asia exhibiting a wide range of social organizations, along with quantitative ethno‐demographic information sampled at the individual level. Results: MtDNA diversity was lower in matrilocal than in multilocal and patrilocal populations while Y chromosome diversity was similar among these social organizations. The reasons for such asymmetry at the genetic level were understood by quantifying sex‐specific migration rates from our ethno‐demographic data: while female migration rates varied between social organizations, male migration rates did not. This unexpected lack of difference in male migrations resulted from a higher flexibility in residence rule in patrilocal than in matrilocal populations. In addition, our data suggested an impact of clan fission process on uniparental genetic patterns. Conclusions: The observed lack of signature of patrilocality on Y chromosome patterns might be attributed to the higher residence flexibility in the studied patrilocal populations, thus providing a potential explanation for the apparent discrepancies between social and genetic structures. Altogether, this study highlights the need to quantify the actual residence and descent patterns to fit social to genetic structures.